Aristotle and Husayn Waiz Kashifi: Harmony in Moral Views - Alimov Akbar Narboyevich (Zien Journals, 2022)
In this country, the influence of the ancient Greek mushils is considered, in the private philosophy of morality of Aristotle, based on the principle of rationality, which is a motivating influence on the moral and philosophical teachings of Husayn Waiz Kashifi
Keywords: ancient Greek philosophy; Aristotle; the concept of ethics; rational principle